The evolution of optimal emergence times: bet hedging and the quest for an ideal free temporal distribution of individuals. Issue 11 (21st March 2016) - Poethke, Hans Joachim; Hovestadt, Thomas; Mitesser, Oliver
Abstract : Proper timing of activities is one of the principal challenges faced by most organisms. Organisms need to account for various aspects in decision making like avoiding inordinate risks, synchronizing with resource availability, or finding mates. We provide analytical and simulation models to investigate the influence of life expectancy, resource competition and unpredictable environmental conditions (environmental uncertainty) on the evolutionarily stable distribution of emergence times in organisms depending on seasonally available resources. We focus on the partitioning of total phenotypic variance in emergence times into 1) genetic variance in mean emergence times between lineages and 2) environmental trait variance that determines the intra‐lineage variance in the timing of emergence. Both, life expectancy of organisms and intensity of competition severely influence the evolutionary response to environmental uncertainty. Our main findings can be summarized as follows: 1) in general diversifying bet hedging (environmental trait variance) is the adequate mechanism to reduce the risk arising from environmental uncertainty while conservative bet hedging, i.e. delaying emergence into 'safe' phases of the season is restricted to short lived organisms and to situations with vanishing competition. 2) Environmental trait variance increases with increasing environmental uncertainty whereas 3) significant genetic variance evolves only under severe resource competition; it is driven by selection for an ideal free distribution of emergence times. 4) The level of genetic variance evolving declines with increasing life expectancy of organisms. 5) With sufficiently short life expectancy evolutionary branching and coexistence of distinctly different emergence strategies occurs; the number of co‐occurring strategies is determined by the level of environmental uncertainty. Our model provides cues for understanding how different ecological factors contribute and interact to shape the evolution of emergence strategies.